State Capacity as an Organizational Problem - Mastrorocco, Nicola; Teso, Edoardo (Review of Economic Studies, 2026)
We investigate how technologies that reduce the costs of monitoring by central authorities have shaped the historical transition from small patrimonial states to large bureaucratic organizations. Our analysis is based on a novel dataset that traces changes in the organizational structure and geographic presence of the U.S. federal government over the nineteenth century. To identify causal effects, we develop a new identification strategy that exploits the expansion of the railroad network as a source of variation in the travel time–and thus monitoring costs–between Washington D.C. and other locations. We present three main findings. First, reductions in travel time to Washington D.C. significantly increased the likelihood of federal government presence in a location. Second, this effect is stronger for occupations and tasks characterized by more severe agency problems. Third, decreases in travel time to Washington D.C. are associated with a decline in patrimonial features of the federal government in the location, in line with enhanced monitoring capacity reducing dependence on personal trust and connections.